The Effect Of Giving Plant Growth Promoting Rhizobacteria (PGPR) On The Growth Of Mustard Plants (Brassica juncea L.) - Ogie, Tommy Bartholomeus; Dawan, Mukatemun; Kaligis, James Bright (Sam Ratulangi University, 2024)
This research was carried out at the Green House of the Faculty of Agriculture, Sam Ratulangi University, Manado, North Sulawesi in March-May 2023. This research was conducted at the Green House of the Faculty of Agriculture, Sam Ratulangi University, Manado, North Sulawesi in March-May 2023. The tools used in this research were polybags measuring 35 x 35 (5 kg/polybag of soil), shovels, gembor, label paper, stationery, a ruler, a view tray, and a camera. The materials used in this study were soil, cocopeat, PGPR, water, and mustard seeds. The research method used was a completely randomized design (CRD) method with 5 treatments and 4 x treatment repetitions so that the number obtained was 20 plants with PGPR concentration treatment, namely: P0: Without PGPR, P1: Concentration of 20 cc/liter of water, P2: Concentration 40 cc/liter of water, P3: Concentration of 60 cc/liter of water, P4: Concentration of 80 cc/liter of water. Observations made included plant height, number of seeds, plant fresh weight, and root length. The data obtained were analyzed using a test of variance (ANOVA) and continued with a BNT test at the 5% level. Based on the results of the study, it can be concluded that giving PGPR 40cc/liter of water and 80cc/liter of water can increase the number of leaves in the second week by 7.5 strands, however giving PGPR has no effect on plant height, plant fresh weight and root length. Keywords: Plant Growth Promoting Rhizobacteria (PGPR), Tanaman Sawi (Brassica juncea L.) Abstrak Penelitian ini dilaksanakan di Rumah Kaca Fakultas Pertanian Universitas Sam Ratulangi Manado Sulawesi Utara pada bulan Maret-Mei 2023. Penelitian ini dilaksanakan di Rumah Kaca Fakultas Pertanian Universitas Sam Ratulangi Manado Utara Sulawesi pada bulan Maret-Mei 2023. Alat yang digunakan dalam penelitian ini adalah polibag berukuran 35 x 35 (5 kg/polibag tanah), sekop, gembor, kertas label, alat tulis, penggaris, view tray, dan kamera. Bahan yang digunakan pada penelitian ini adalah tanah, cocopeat, PGPR, air, dan biji sawi. Metode penelitian yang digunakan adalah dengan menggunakan metode Rancangan Acak Lengkap (RAL) dengan 5 perlakuan dan 4 x ulangan perlakuan sehingga diperoleh jumlah 20 tanaman dengan perlakuan konsentrasi PGPR yaitu : P0 : Tanpa PGPR, P1 : Konsentrasi 20 cc/liter air, P2 : Konsentrasi 40 cc/liter air, P3 : Konsentrasi 60 cc/liter air, P4 : Konsentrasi 80 cc/liter air. Pengamatan yang dilakukan meliputi tinggi tanaman, jumlah benih, bobot segar tanaman dan panjang akar. Data yang diperoleh dianalisis dengan menggunakan uji variansi (ANOVA) dan dilanjutkan dengan uji BNT pada taraf 5%. Berdasarkan hasil penelitian dapat disimpulkan bahwa pemberian PGPR 40cc/liter air dan 80cc/liter air dapat meningkatkan jumlah daun pada minggu kedua sebanyak 7,5 helai, namun pemberian PGPR tidak memberikan pengaruh terhadap tinggi tanaman, bobot segar tanaman dan panjang akar. Kata Kunci: Plant Growth Promoting Rhizobakteria (PGPR), Tanaman Sawi (Brassica juncea L.)